Prostaglandin F(2α) Metabolite Levels Following an Embryo Transfer Procedure in the Mare - Kask, K. (Acta Vet Scand, 1995)
Hormonal, chemical, and mechanical stimuli can activate the arachidonic acid cascade and result in formation of prostaglandins and related substances. These compounds can have a profound role in the initiation of the inflammatory process (Higgins & Lees 1984). Prostaglandin (PG) F(2α) is the key hormone in reproductive physiology with well-known effects on reproductive performance e.g. luteolysis and abortion. An activation of the arachidonic acid cascade, caused by mechanical manipulation during an embryo transfer procedure, might be one explanation for early embryonic loss.